Venice and the Veneto during the Renaissance: the Legacy of Benjamin Kohl - Law, John Easton; Smith, Alison A.; KNAPTON, Michael William (Reti Medievali E-Book, 2014)
Benjamin G. Kohl (1938-2010) taught at Vassar College from 1966 till his retirement as Andrew W. Mellon Professor of the Humanities in 2001. His doctoral research at The Johns Hopkins University was directed by Frederic C. Lane, and his principal historical interests focused on northern Italy during the Renaissance, especially on Padua and Venice. His scholarly production includes the volumes Padua under the Carrara, 1318-1405 (1998), and Culture and Politics in Early Renaissance Padua (2001), and the online database The Rulers of Venice, 1332-1524 (2009). The database is eloquent testimony of his priority attention to historical sources and to their accessibility, and also of his enthusiasm for collaboration and sharing among scholars.